Inggris - Tahir, Takdir; Putri, Egi Trisnayanti (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Hypospadias is a birth defect found in baby boys, where the position of the external urethral meatus does not open at the tip of the penis but is located on the ventral surface of the penis. Hypospadias is classified based on the position or location of the abnormal external urethral meatus. The treatment that can be done for hypospadias patients is surgery. In general, surgery is carried out in two stages, namely chordectomy and urethroplasty. There are various surgical techniques that can be performed on hypospadias patients. This is adjusted to the position or location of the hypospadias and the abilities of the surgical operator. The aim of this study is to determine the difference in duration of surgery based on the location of the hypospadias. The method used was descriptive analytic with a case study approach by comparing the duration of urethroplasty surgery with the location of hypospadias in patients with a medical diagnosis of hypospadias who underwent urethroplasty surgery. The results showed that there was a significant difference in the duration of surgery in patients whose hypospadias was in the distal penile position and in patients whose hypospadias was in the scrotal position, even though they used the same surgical technique, namely Tubularized Incised Plate (TIP).